Pemetaan Tingkat Kerawanan Longsor Berbasis Sistem Informasi Geografis (SIG) di Wilayah Kota Bandung Provinsi Jawa Barat - Yuannita, Yuannita; Arifin, Dawamul; Kurniadin, Nia; Insanu, Radik Khairil (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
Landslides are one of the most frequent and destructive natural disasters in West Java Province, particularly in Bandung City, which is characterized by varied topography, high rainfall, and rapid land-use change. This study aims to analyze and map the spatial distribution of landslide susceptibility in Bandung City using the Weighted Overlay method based on Geographic Information Systems (GIS). Five parameters were applied in the analysis: slope, rainfall intensity, soil type, rock type, and land use. Each parameter was classified and weighted according to its influence on landslide occurrence. The analysis revealed that the landslide susceptibility levels in Bandung vary from low to very high. The largest area, covering 49.88%, falls within the moderate susceptibility class, while 36.02% of the area is categorized as high to very high susceptibility. High rainfall intensity and extensive land-use conversion in hilly regions were identified as the dominant contributing factors to landslide potential, supported by steep slopes and easily weathered geological formations. The resulting susceptibility map provides essential spatial information for local government authorities in developing sustainable land-use planning, risk mitigation strategies, and community preparedness programs. The study highlights the effectiveness of GIS-based analysis for environmental hazard assessment and emphasizes the need for high-resolution data integration in future research to improve mapping accuracy.